The Relationship Between Religiusity And Affective Commitmen on Ikatan Mahasiswa Muhammadiyah - Mohammad Thursin Aji; Widyastuti Widyastuti (Indonesian Journal of Islamic Studies, 2021)
This research is a study of the phenomenon of affective commitment experienced by IMM students, Muhammadiyah University of Sidoarjo. The purpose of this study was to determine the relationship between religiosity and affective commitment in IMM students, Muhammadiyah University of Sidoarjo. The type of research used is quantitative research with a correlational approach. This study uses two variables, namely the religiosity variable as the independent variable and the affective commitment variable as the dependent variable. This research was conducted at the University of Muhammadiyah Sidoarjo on 172 IMM Students (Muhammadiyah Student Association) using the Convenience Sampling technique. The data collection technique used two psychological scales with a Likert scale model, namely the religiosity scale and the affective commitment scale. The results of the reliability coefficient of Alpha Cronbach's religiosity scale of 0.935 with a total of 35 valid items, while the results of the reliability coefficient of Alpha Cronbach's affective commitment scale of 0.957 with a total of 48 valid items. The analysis used is the Pearson Product Moment correlation analysis technique using the SPSS 20 for windows program. The results of the correlation coefficient analysis showed the results of 0.370 with a significance of 0.000. So that it is stated that there is a positive relationship between religiosity and affective commitment to IMM students, Muhammadiyah University of Sidoarjo, this shows that the initial hypothesis proposed by the researcher is accepted. The result of the effective contribution between the variables of religiosity and affective commitment is 13.7%.